Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan Property Dan Real Estate (Jurnal Paradigma Akuntansi, 2022)
This research aims to test empirically the effect of firm size, growth, tangibility, liquidity, and profitability on the capital structure on property and real estate companies listed in the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and the valid data was 40 companies. Data processing techniques using multiple regression analysis with Eviews statistical tool. The results showed that company size, growth, and liquidity had a negative effect on capital structure. Furthermore, tangibility and profitability did not have effect on capital structure. This research has important policy implications for the finance managers of property and real estate companies.